THE EFFECTIVENESS OF PEER REVIEWING TECHNIQUE IN TEACHING WRITING IN NARRATIVE TEXT AT GRADE VIII SMP N 1 SEI RAMPAH - Renata Elisabet Siringo-ringo; Fenty Debora Napitupulu; Carolina Pakpahan (Sean Institute, 2023)
This study aimed to determine the effectiveness of Peer Reviewing techniques in teaching writing abilities. This research aims to see whether Peer Reviewing Technique impacts students' ability to write narrative text. This investigation was carried out using experimental quantitative research. The research subject was SMP Negeri 1 Sei Rampah. The researcher applies the Peer Reviewing technique to the VIII-1 experimental class, which consists of 30 students; the control class uses the conventional VIII-2 method, which consists of 30 students. There are 60 students in this study, divided into two classes. The researcher chose two classrooms as samples to investigate the effectiveness of Peer-reviewing techniques in improving writing skills. Data was collected by giving tests to determine whether students understand the content. Both the experimental class and the control class were given two tests, namely: pre-test and post-test. The average pre-test value in the experimental class was 66.9, and the post-test was 81.3. The average value of the pre-test in the control class was 67.2, and the post-test was 76.8. It was found that the average value of the experimental class was greater than the control class. The t count > t table results in a significance level of p = 0.05 (4.42 > 2.048). The null hypothesis (Ho) is rejected, while the alternative hypothesis (Ha) is accepted. In other words, from this research, it is known that peer review techniques can influence the students' narrative text writing ability. It can be concluded that there is a significant effectiveness of using peer review techniques towards students' narrative text writing ability.